Dato' Vijay Kumar Natarajan & Anor lwn Malaysia Airlines Bhd. [2021] MLJU 407: (Dato' Vijay Kumar Natarajan & Anor v. Malaysia Airlines Bhd.) (Kanun: Jurnal Undang-undang Malaysia, 2022)
-Teks penuh: PDF